Focus Group Discussion and Workshop on Exploring the Tourism Potential of Jumpinang River Tubing Pasuruan - Ramanda, Pramadika; Atmoko, Rachmad Andri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service program aims to improve the quality of management and promotion of Jumpinang River Tubing tourist destinations in Pasuruan through the use of digital technology. Implementation methods include problem identification, website creation, and guiding and safety training for local communities. This process was carried out for 3 months, with core activities in the form of Focus Group Discussion (FGD), website development, and technical training. The results of the program show that the community's capacity is increased in the management of tourist destinations, as well as the ease of promotion through digital platforms. The implication of this program is the increase in the number of tourist visits and the strengthening of the sustainability of tourism management by the community.